Concept Analysis of Self-Care Strategies in Schizophrenia - Dessy Dwi Cahyaningrum; Meidiana Dwidiyanti; Titik Suerni (Jurnal Ilmu Keperawatan Jiwa, 2020)
Schizophrenic patients will experience an inability to care for themselves. This has an impact on cognitive impairment. Therefore the self-care strategy of schizophrenic patients is very important and must be assessed by nurses regularly. The purpose of this paper is to analyze the concept, clarify the meaning of the concept of self-care strategies in schizophrenia. The concept analysis procedure from Walker and Avant is used in this paper. Literature reviews are conducted using online databases, such as Sciencedirect, Pubmed, Google Scoolar and the scientific journal of health, with the keywords "schizophrenia and self-care strategies". The publication year of the articles used is 2010 to 2020. The articles used was 5 articles. The concept of self-care strategies is very important for schizophrenia patients, so that patients can be confident in their self-care abilities and achieve the independence goals of ADL (Activity of Daily Living). Antecendent of the concept of self-care strategies in schizophrenia: patients experience symptoms of decreased self-care, individual reactions to symptoms, and severity of symptoms and duration of symptoms. Concept attributes: self-care behavior, self-confidence, self-study, and trial and error. The consequences of the concept: lead to the reduction of symptoms, reduction in the incidence or prevention of symptoms and in general that is an increase in health status, the ability to carry out activities of daily life.